2016
DOI: 10.1074/mcp.m116.058016
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Omics and Computational Glycobiology Reveal Structural Basis for Influenza A Virus Glycan Microheterogeneity and Host Interactions

Abstract: Despite sustained biomedical research effort, influenza A virus remains an imminent threat to the world population and a major healthcare burden. The challenge in developing vaccines against influenza is the ability of the virus to mutate rapidly in response to selective immune pressure. Hemagglutinin is the predominant surface glycoprotein and the primary determinant of antigenicity, virulence and zoonotic potential. Mutations leading to changes in the number of HA glycosylation sites are often reported. Such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 123 publications
(166 reference statements)
9
118
0
Order By: Relevance
“…Albumin and IgG were depleted using ProteoExtract® Albumin/IgG Removal Kit (EMD Millipore, Billerica MA). Depleted serum and glycoprotein mixes were subjected to sample preparation and analysis using a multi-pronged approach, as described previously [28]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin and IgG were depleted using ProteoExtract® Albumin/IgG Removal Kit (EMD Millipore, Billerica MA). Depleted serum and glycoprotein mixes were subjected to sample preparation and analysis using a multi-pronged approach, as described previously [28]. …”
Section: Methodsmentioning
confidence: 99%
“…A Waters™ Xbridge™ reversed-phase column (150 μm × 100 mm) with 1.7 μm BEH C18 resin and a Waters™ trap column (180 μm × 20 mm) packed with 5 μm Symmetry™ C18 stationary phase were used for online desalting and separation of the proteomics samples. The mass spectrometer was programmed to acquire data-dependent tandem MS, using instrument parameters described previously [28]. Glycoproteins used in complexity mixtures were analyzed both individually and as mixtures of increasing complexity.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of site-specific microheterogeneity on a protein with multiple N-glycosylation sites in cell or tissue-derived extracts requires more elaborate analytical methods that have become available only recently (16,17,(34)(35)(36). Few studies have shown the relation between protein primary sequence and the observed glycan profile.…”
mentioning
confidence: 99%
“…This incomplete processing can therefore be modulated by altering the reaction-limiting parameters, such as enzyme and substrate concentrations, enzyme-substrate exposure time, and substrate affinities (13)(14)(15). In addition, properties of the N-glycoprotein itself, such as accessibility of the N-glycan to the processing machinery can result in differential site-specific glycan structures (16,17).…”
mentioning
confidence: 99%
“…As such, this research contributes novel results of glycans produced in embryonic eggs. (47,287,298). The observation of Sulf on NDV HN glycans is likely due to propagation methods.…”
Section: Overview Of the Results With Reference To Current Literaturementioning
confidence: 99%